2018
DOI: 10.5146/tjpath.2018.01425
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2, endothelin-1, and cd34 as biomarkers of aggressive cervical squamous cell carcinoma: an immunohistochemical study

Abstract: Objective: Cervical cancer has an increasing incidence in developing countries with a predominance of squamous cell carcinoma. In this work, we aimed to analyze the role of EZH2, Endothelin-1, and CD34 as indicators of the aggressiveness in cervical squamous cell carcinoma. Material and Method:Immunohistochemical expression of EZH2, Endothelin-1, and CD34 was studied in 54 paraffin-embedded tissue specimens of cervical squamous cell carcinoma. Their correlation to the clinicopathologic features and the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…CD34 is a transmembrane glycoprotein expressed in a vascular endothelial cell that has been used as a direct marker to highlight the microvascular density [21]. An immunohistochemical study was shown that high CD34 expression was significantly associated with tumor size, tumor stage and lymph node metastasis in cervical cancer [22]. The present study revealed a positive relationship between the pre-NACT expression of CD34 and the efficacy of NACT in cervical cancer.…”
Section: Discussionsupporting
confidence: 58%
“…CD34 is a transmembrane glycoprotein expressed in a vascular endothelial cell that has been used as a direct marker to highlight the microvascular density [21]. An immunohistochemical study was shown that high CD34 expression was significantly associated with tumor size, tumor stage and lymph node metastasis in cervical cancer [22]. The present study revealed a positive relationship between the pre-NACT expression of CD34 and the efficacy of NACT in cervical cancer.…”
Section: Discussionsupporting
confidence: 58%
“…CD34 is a sialomucin family-related transmembrane protein that is involved in the modulation of cell adhesion and signal transduction (42). While it was first identified as a hallmark of hematopoietic stem cells, studies demonstrated that CD34 is also present on nonhematopoietic cell lines, including embryonic fibroblasts and vascular endothelial progenitors (43).…”
Section: Discussionmentioning
confidence: 99%
“…CD34 is a sialomucin family-related transmembrane protein that is involved in the modulation of cell adhesion and signal transduction. 38 While it was first identified as a hallmark of hematopoietic stem cells, studies demonstrated that CD34 is also present on nonhematopoietic cell lines, including embryonic fibroblasts and vascular endothelial progenitors. 39 Here we used CD34+ CD45-to sort subpopulations of tumor cells using flow cytometry as the most effective approach towards enriching stem-like tumor cells, thereby eliminating hematopoietic stem cells which are CD34+CD45+.…”
Section: Discussionmentioning
confidence: 99%